2011
DOI: 10.1074/jbc.m110.179572
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-specific Up-regulation of Apolipoprotein E Gene Expression by STAT1 Is Achieved via Long Range Genomic Interactions

Abstract: In atherogenesis, macrophage-derived apolipoprotein E (apoE) has an athero-protective role by a mechanism that is not fully understood. We investigated the regulatory mechanisms involved in the modulation of apoE expression in macrophages. The experiments showed that the promoters of all genes of the apoE/apoCI/apoCIV/apoCII gene cluster are enhanced by multienhancer 2 (ME.2), a regulatory region that is located 15.9 kb downstream of the apoE gene. ME.2 interacts with the apoE promoter in a macrophage-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 58 publications
(57 reference statements)
1
28
0
Order By: Relevance
“…These enhancers are located at 3.3 and 15.9 kb downstream of the apoE gene, respectively. We demonstrated by chromosome conformational capture (3C) and transient transfections that both ME.1 and ME.2 can interact with the apoE promoter only in phorbol 12-myristate 13-acetate (PMA)-differentiated macrophages, but not in undifferentiated monocytes (Trusca et al 2011). The results showed that the interactions take place in antisense orientation of the promoter and ME.1/2.…”
Section: Distal Regulatory Binding Sites That Modulate Apoe Genementioning
confidence: 97%
“…These enhancers are located at 3.3 and 15.9 kb downstream of the apoE gene, respectively. We demonstrated by chromosome conformational capture (3C) and transient transfections that both ME.1 and ME.2 can interact with the apoE promoter only in phorbol 12-myristate 13-acetate (PMA)-differentiated macrophages, but not in undifferentiated monocytes (Trusca et al 2011). The results showed that the interactions take place in antisense orientation of the promoter and ME.1/2.…”
Section: Distal Regulatory Binding Sites That Modulate Apoe Genementioning
confidence: 97%
“…3A) 70 . Both ME.1 and ME.2 are required for APOE gene expression in macrophages, adipose tissue, and brain 71, 72 .…”
Section: Transcriptional Control Of the Human Apoc2 Genementioning
confidence: 99%
“…The apoE proximal promoter [-500/+73]apoE-luc and its deletion mutants: [-200/+73]apoE-luc, [-100/+73]apoE-luc and [-55/+73]apoE-luc, previously described [16, 17], were cloned in KpnI/XhoI sites in pGL4 vector (Promega). GR_synthRE (S900015) reporter construct (which contains a synthetic glucocorticoid response element) was purchased from SwitchGear Genomics (Belgium), and the pcDNA3-hGRα plasmid was kindly provided by Dr. Russcher (University Medical Center, Rotterdam).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, two multienhancer regions, namely ME.1 and ME.2, were found to regulate apoE expression in macrophages and adipose tissue [14]. Previous studies showed that apoE gene transcription increased upon monocyte differentiation into macrophages [15, 16]. On the other hand, the inflammatory conditions (such as those induced by lipopolysaccharides) lead to a decrease in apoE expression in macrophages [17], a process with negative consequences on cholesterol efflux from the atherosclerotic plaque.…”
Section: Introductionmentioning
confidence: 99%